2006
DOI: 10.1111/j.1537-2995.2006.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of 44 assays used in countries with limited resources for the detection of antibodies to hepatitis C virus

Abstract: On applying criteria for highest sensitivity (100%) and high specificity (> or =99.5%), 11 tests met the criteria. An additional 19 tests reached a performance comparable to WHO's criteria for human immunodeficiency virus antibody assays. The genotype diversity of HCV was found not to influence sensitivity of the assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 12 publications
1
34
0
3
Order By: Relevance
“…In our study both assays showed no problems concerning their specificity neither with the investigated routine samples nor with the additionally tested samples from pregnant women or with samples positive for IgM-antibodies. The ARCHITECT results were highly comparable to those of the Ortho assay, which has proved to be highly specific and sensitive as shown in other studies (Oethinger et al, 2005;Zachary et al, 2005;Scheiblauer et al, 2006;Watterson et al, 2007). Analysis of the 38 samples that were discordant between the Ortho and ARCHITECT assays revealed a great variance in the two supplemental immunoblot assays (Inno-LIA and RIBA).…”
Section: Discussionsupporting
confidence: 69%
“…In our study both assays showed no problems concerning their specificity neither with the investigated routine samples nor with the additionally tested samples from pregnant women or with samples positive for IgM-antibodies. The ARCHITECT results were highly comparable to those of the Ortho assay, which has proved to be highly specific and sensitive as shown in other studies (Oethinger et al, 2005;Zachary et al, 2005;Scheiblauer et al, 2006;Watterson et al, 2007). Analysis of the 38 samples that were discordant between the Ortho and ARCHITECT assays revealed a great variance in the two supplemental immunoblot assays (Inno-LIA and RIBA).…”
Section: Discussionsupporting
confidence: 69%
“…The quality of test kits used for anti-HCV testing may be a reason for concern, since some test kits used in limited-resource countries including India has been found to be unsatisfactory. 131,132 Use of nucleic acid testing (NAT) has been evaluated for preventing transmission of HCV as well as other blood borne pathogens (human immunodeficiency virus-1 and hepatitis B virus) in Indian blood donors has been proposed. It has been estimated that NAT could interdict 3272 infections annually among nearly 5 million annual donations.…”
Section: Provision Of Safe Blood and Blood Productsmentioning
confidence: 99%
“…In US populations, the sensitivity and specificity of anti-HCV detection is considered to be very high using third generation assays that require multiple antigens including HCV NS5 protein and these assays have been standard of care for some time [Allain, 1998;Ghany et al, 2009]. The performance of EIAs in Africa has not been well defined [Rouet et al, 2004;Hladik et al, 2006;Scheiblauer et al, 2006;Desbois et al, 2008]. The price and requirement for complex equipment significantly limit wider use of EIA in the developing world.…”
Section: Introductionmentioning
confidence: 98%